Reward and Consumer Brand Engagement: Building Brand Loyalty in The On-Demand Service Platform - Hidayat, Desman; Selviana; Alfaizah, Muhamad Agung; Rumangkit, Stefanus; Pratiwi, Chairani Putri (Indonesian Journal of Business and Entrepreneurship, 2024)
Background: The on-demand service platform is an uprising business that has become more popular recently. Nevertheless, the competition within this industry can make it hard for companies to survive. Therefore, brand loyalty is vital to ensure the business survives the competition. Purpose: This study investigates how reward and consumer brand engagement can affect brand loyalty in the on-demand service industry. Design/methodology/approach: Empirical evidence was collected using a quantitative method using convenience sampling from 232 users of Indonesia’s most significant on-demand service industry. This study used Structural Equation Modeling (SEM). Findings/Result: The results of this study show that reward and consumer brand engagement both have positive and significant effects on brand loyalty. Furthermore, consumer brand engagement also mediates the relationship between reward and brand loyalty of the customers. Conclusion: Therefore, it is crucial for on-demand service platforms to improve their reward system for the customer and to pay more attention to their consumer brand engagement to improve brand loyalty.Originality/value (State of the art): Only a few articles use rewards in gamification in a business context. Keywords: brand loyalty, consumer brand engagement, gamification, on-demand service platform, reward